2001
DOI: 10.1074/jbc.m010727200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship Studies of Melanin-concentrating Hormone (MCH)-related Peptide Ligands at SLC-1, the Human MCH Receptor

Abstract: Melanin-concentrating hormone (MCH) is a cyclic nona- Melanin-concentrating hormone (MCH)1 has been initially described in fish as a heptadecapeptide (Asp-Thr-Met-Arg-CysMet-Val-Gly-Arg-Val-Tyr-Arg-Pro-Cys-Trp-Glu-Val (1)). Its structure was relatively conserved throughout evolution, although in mammals the sequence of MCH is a nonadecapeptide with differences mainly in the N terminus (Asp-Phe-Asp-MetLeu-Arg-Cys-Met-Leu-Gly-Arg-Val-Tyr-Arg-Pro-Cys-Trp-GlnVal (2)). In rodents, there are now several lines of evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 51 publications
(68 reference statements)
6
63
1
1
Order By: Relevance
“…Aequorin Bioluminescence Functional Assays (24,26,27)-For the functional receptor activation assays, stable cell lines expressing either the MCH-1R or the MCH-2R and the aequorin reporter protein were used. The assays were performed on a Luminoskan RT luminometer (Labsystems Inc., Gaithersburg, MD) controlled by custom software written for a PC-compatible computer.…”
Section: Methodsmentioning
confidence: 99%
“…Aequorin Bioluminescence Functional Assays (24,26,27)-For the functional receptor activation assays, stable cell lines expressing either the MCH-1R or the MCH-2R and the aequorin reporter protein were used. The assays were performed on a Luminoskan RT luminometer (Labsystems Inc., Gaithersburg, MD) controlled by custom software written for a PC-compatible computer.…”
Section: Methodsmentioning
confidence: 99%
“…The Sphyrna MCH peptide is composed of 19 AA and is identical to the mammalian MCH, except for a C-terminal residue. A ring structure formed by a disulfide bond, an Arg residue in the N-terminal side chain, and a Trp residue in the C-terminal tail of human MCH are essential for the binding of the protein to its receptor [4]. This structure is well conserved in Sphyrna MCH, suggesting that this peptide might be functional in the shark.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that shortened cyclic peptides on the N-or C-terminal parts could be still active in the rat brain. In contrast, linear compound or deletion in the ring structure led to complete inactivity in binding/functional assays using MCH 1 -transfected cells and in fish or rat bioassays (Audinot et al, 2001a;Bednarek et al, 2001;). This allows us to consider endopeptidase 24.11 and related enzymes as overt MCH-inactivating peptidases.…”
Section: Discussionmentioning
confidence: 99%
“…Because NEI-MCH acts as a superagonist, we hypothesized that it may be a better ligand or activator of signaling pathways than MCH at either of the MCH receptors. Previous studies have identified the structural domains of MCH responsible for binding and affinity to MCH1 (MacDonald et al, 2000;Audinot et al, 2001a) and MCH2 (Bednarek et al, 2001;Rodriguez et al, 2001). These and Arg 14 as a potential site of interaction with MCH1 and MCH 6 -17 (ring between Cys 7 and Cys 16 ) as a minimal sequence required for an agonistic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation